Candida tropicalis Etr1p and Saccharomyces cerevisiae Ybr026p (Mrf1′p), 2-Enoyl Thioester Reductases Essential for Mitochondrial Respiratory Competence - Torkko, Juha M. (American Society for Microbiology, 2001)
We report here on the identification and characterization of novel 2-enoyl thioester reductases of fatty acid metabolism, Etr1p from Candida tropicalis and its homolog Ybr026p (Mrf1′p) from Saccharomyces cerevisiae. Overexpression of these proteins in S. cerevisiae led to the development of significantly enlarged mitochondria, whereas deletion of the S. cerevisiae YBR026c gene resulted in rudimentary mitochondria with decreased contents of cytochromes and a respiration-deficient phenotype. Immunolocalization and in vivo targeting experiments showed these proteins to be predominantly mitochondrial. Mitochondrial targeting was essential for complementation of the mutant phenotype, since targeting of the reductases to other subcellular locations failed to reestablish respiratory growth. The mutant phenotype was also complemented by a mitochondrially targeted FabI protein from Escherichia coli. FabI represents a nonhomologous 2-enoyl-acyl carrier protein reductase that participates in the last step of the type II fatty acid synthesis. This indicated that 2-enoyl thioester reductase activity was critical for the mitochondrial function. We conclude that Etr1p and Ybr026p are novel 2-enoyl thioester reductases required for respiration and the maintenance of the mitochondrial compartment, putatively acting in mitochondrial synthesis of fatty acids.